1956
DOI: 10.1128/jb.72.5.681-689.1956
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Fatty Acid Forming Organism Isolated From the Rumen of Sheep

Abstract: Three organisms, Clostridium kluyveri (Barker and Taha, 1942), Rhodospirillum rubrm (Kohlmiller and Gest, 1951) and an organism isolated from silage by Rosenberger (1952) and identified as Clotridium scatologenes, have been shown to synthesize fatty acids higher than n-butyrate, as end products of fermentative metabolism. In this paper we give an account of the isolation and properties of an anaerobic, gram negative organism which ferments certain carbohydrates and DL-lactic acid with the formation of hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 22 publications
5
68
0
Order By: Relevance
“…The level of JCM at the cecum decreased to the 10 8 /pouch (10 7 /g digesta)‐level in that study but still worked efficiently. JCM is of ovine rumen origin (Elsden et al . 1956); therefore, this strain had not been checked to determine if it is resistant to gastric LAB and gastro‐intestinal digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The level of JCM at the cecum decreased to the 10 8 /pouch (10 7 /g digesta)‐level in that study but still worked efficiently. JCM is of ovine rumen origin (Elsden et al . 1956); therefore, this strain had not been checked to determine if it is resistant to gastric LAB and gastro‐intestinal digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The reactor was purged with high-purity (99.999%) nitrogen gas to guarantee anaerobic conditions after it was sealed. The basic culture medium per liter contained NaHCO 3 , 5,040 mg; NH 4 12 , 0.001 mg; and lipoic acid, 0.05 mg. All the chemicals used in the study were of analytical grade or better.…”
Section: Methodsmentioning
confidence: 99%
“…E. pyruvativorans has been reported to harbor metabolic properties analogous to those of C. kluyveri (10). Additionally, n-caproic acid can be produced from lactate by a ruminal Ruminococcaceae bacterium (11) and Megasphaera elsdenii (12).…”
mentioning
confidence: 99%
“…In a review article, Oxford (1958) (1952) concluded that Clostridium pro-plonlcum appears to form propionate from lactate by a more direct mechanism without production of intermediary dlcarboxylic acids and without Involving carbon dioxide fixation followed by subsequent decarboxylation. Elsden et al (1956) isolated an unidentified organism from the rumen of sheep that fermented lactate directly to propionate. Ladd (19 59) con firmed Elsden's observations.…”
mentioning
confidence: 99%